SARS-CoV-2 Associated Pediatric Inflammatory Multisystem Syndrome With a High Prevalence of Myocarditis – A Multicenter Evaluation of Clinical and Laboratory Characteristics, Treatment and Outcome - Thom, Katharina; Kahl, Beatrice; Wagner, Thomas; van Egmond-Fröhlich, Andreas; Krainz, Mathias; Frischer, Thomas; Leeb, Iris; Schuster, Christine; Ehringer-Schetitska, Doris; Minkov, Milen; Male, Christoph; Michel-Behnke, Ina (Frontiers in Pediatrics, 2022)
Introduction Pediatric inflammatory multisystem syndrome - temporally associated with SARS-CoV-2 infection (PIMS –TS) comprises a new disease entity having emerged after the COVID-19 outbreak in 2019. Material and Methods For this multicenter, retrospective study children between 0 and 18 years with PIMS-TS between March 2020 and May 2021 were included, before availability of vaccination for children. Frequent SARS-CoV-2 variants at that period were the wildtype virus, alpha, beta and delta variants. Inclusion criteria were according to the PIMS-TS criteria, proposed by the Royal College of Pediatrics and WHO. Study aim was to review their clinical, laboratory and echocardiographic data with a focus on cardiac involvement. Results We report 45 patients, median age nine years, 64% male. SARS-CoV-2 antibodies were positive in 35/41 (85%). PIMS occurrence followed local Covid-19 peak incidence periods with a time lag. The most common symptoms at presentation were fever (98%), abdominal pain (89%) and rash (80%). Fever history of > 5 days was associated with decreased left ventricular function (p=0.056). Arterial hypotension and cardiac dysfunction were documented in 72% patients, increased brain natriuretic peptide in 96% and increased cardiac troponin in 64% of the children. Echocardiography revealed mitral valve regurgitation (64%), coronary abnormalities (36%) and pericardial effusions (40%). Increased NT-proBNP was significantly associated with the need of inotropics (p<0.05), which were necessary in 40% of the patients. Treatment comprised intravenous immunoglobulin (93%), systemic steroids (84%) and acetylsalicylic acid (100%; 26/45 started with high dosages). For insufficient response to this treatment, five (11%) children received the interleukin-1 receptor antagonist anakinra. All patients were discharged with almost resolved cardiac signs. Conclusion: Our analysis of non-vaccinated children with PIMS-TS demonstrates that a considerable number have associated myocarditis requiring intensive care and inotropic support. Most children showed adequate response to intravenous immunoglobulin and steroids and good recovery. Further evaluation of pediatric patients with Covid-19 associated diseases is required to evaluate the impact of new virus variants.